Represivitas Negara Terhadap Komuniti Bangsa - - Yusdani (Millah: Journal of Religious Studies, 2006)
The article below tries to trace the roots of state violence toward the communities in Indonesia. The case of Act No. 5 year 1979 regarding the Community (desa, marga, nagari and so on). Government denotes an example of State dominant intervention to communities. This polity has emerged the negative impacts, for instance destructing creative social energy of society, contradicting to self government, and contrary to democracy and the justice principles. The polity of state to regulate and unify the form of community government could be called a kind of the state terror ism. Hence, it is urgent to deconstruct, reconstruct and criticizes the possibilities state re-regulate the similar cases in reformation era nowadays either by accident or by design.